2012
DOI: 10.33549/physiolres.932362
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hind Paw Epidermal Thickness, Peripheral Nerve Distribution and Mechanical Sensitivity After Immobilization in Rats

Abstract: This study was designed to investigate histological changes in skin tissue accompanying immobilization-induced hypersensitivity. Changes in mechanical sensitivity, epidermal thickness, and peripheral nerve profiles in the upper dermis were examined in glabrous skin of rat hind paw after 1, 2, and 4 weeks of ankle joint immobilization by plaster casts. Induction of mechanical hypersensitivity was confirmed after 2 and 4 weeks of joint immobilization. Epidermal thinning and increase in peripheral nerve profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…We found that the PPT of the gastrocnemius muscle in the IM group significantly decreased unilaterally at 2 weeks after immobilization, and this decrease continued up to 4 weeks after immobilization. This PPT change in the skeletal muscle was almost the same as that seen in the skin using von Frey filament during cast immobilization in previous studies . However, because we measured the PPT of the skeletal muscle using the Randall‐Selitto apparatus through the skin, skin hyperalgesia may have also contributed in the IM group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found that the PPT of the gastrocnemius muscle in the IM group significantly decreased unilaterally at 2 weeks after immobilization, and this decrease continued up to 4 weeks after immobilization. This PPT change in the skeletal muscle was almost the same as that seen in the skin using von Frey filament during cast immobilization in previous studies . However, because we measured the PPT of the skeletal muscle using the Randall‐Selitto apparatus through the skin, skin hyperalgesia may have also contributed in the IM group.…”
Section: Discussionsupporting
confidence: 72%
“…We previously investigated the underlying mechanisms of immobilization‐induced pain using a rat model. Two weeks of cast immobilization induced superficial pain in the skin, which was exacerbated when the immobilization period was prolonged . The mechanisms underlying the immobilization‐induced pain are likely associated with upregulation of nerve growth factor (NGF) and increased density of peripheral nerve fibers in the skin …”
Section: Introductionmentioning
confidence: 99%
“…The restrainer allowed the animal to dangle safely and to positions their legs freely without the burden of their weight [13]. Rats were placed individually in the restrainer after their casts were removed and allowed to acclimate for 20 min in a quiet room that was maintained at 24°C.…”
Section: Behavior Testsmentioning
confidence: 99%
“…The current study examined the effects of CPM that was initiated after the onset of arthritis on inflammation and pain-related behavior in rats. In previous studies, the carrageenan model was commonly used for experimental joint inflammation (Okamoto et al 1999, Radhakrishnan et al 2003 because of plasma extravasation after the release of neuropeptides (Lam and Ferrell 1993) and other inflammatory mediators, such as prostaglandins (Nantel et al 1999), and bradykinin (Birrell et al 1993). These noxious chemicals sensitize primary afferent fibers resulting in primary and secondary hyperalgesia Schmidt 1988, Radhakrishnan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In order to follow the changes in joint swelling over time, we measured the transverse diameter of the right knee joint using a manual caliper. Rats were placed individually in a homemade restrainer (Nakano et al 2012) so that loading on the right hind limb was avoided and the knee joint was held in the maximum extended position.…”
Section: Knee Joint Swellingmentioning
confidence: 99%